Diffuse myocardial fibrosis precedes impairment of myocardial strain in patients with systemic sclerosis. (13th July 2021) - Gotschy, A; Jordan, S; Stoeck, CT; Von Deuster, C; Gastl, M; Vishnevskiy, V; Wissmann, L; Dobrota, R; Mihai, C; Becker, MO; Maurer, B; Kozerke, S; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background - Myocardial involvement is common in patients with systemic sclerosis (SSc) and causes myocardial fibrosis and subtle ventricular dysfunction. However, the temporal onset of myocardial involvement during the progression of the disease is yet unknown. Purpose - To investigated the presence of subclinical functional impairment and diffuse myocardial fibrosis in patients with very early diagnosis of SSc (VEDOSS) and to compared the findings to patients with established SSc and healthy controls. Methods - 110 SSc patients (86 with established SSc and 24 with VEDOSS) and 15 healthy controls were prospectively recruited. The study subjects underwent cardiovascular magnetic resonance on a clinical 1.5T system. Pre- and post-contrast T1 mapping was performed using a MOLLI (Modified Look-Locker Inversion Recovery) sequence. For extracellular volume (ECV) measurements, a single bolus protocol with image acquisition 15-20 min. post-contrast injection was used. For the assessment of subtle functional impairment, global longitudinal (GLS) and circumferential (GCS) myocardial strain were evaluated. Results - Native T1 values and ECV were elevated in VEDOSS and in patients with established SSc compared to controls (p < 0.001; Figure 1 A & B). GLS was similar in VEDOSS and controls but significantly reduced in patients with established SSc (p < 0.001; Figure 1 C). GCS was similar over all groups (p = 0.88). Patients with clinical evidence of pulmonary or gastrointestinal involvement had higher ECV or T1 values, respectively. Patients with clinical signs of cardiac involvement had lower absolute GLS. SSc subtype, classification or disease duration were not associated with the extent of myocardial fibrosis or impaired strain. Conclusion - Subclinical myocardial involvement first manifests as diffuse myocardial fibrosis identified by expansion of ECV and increased native T1 in VEDOSS patients while subtle functional impairment as measured by GLS only occurs in established SSc. No single clinical feature of SSc shows a strong association with subtle myocardial involvement.